Investigation of the toxic effects of different polystyrene micro-and nanoplastics on microalgae Chlorella vulgaris by analysis of cell viability, pigment content, oxidative stress and ultrastructural changes. (July 2020) - Hazeem, Layla J.; Yesilay, Gamze; Bououdina, Mohamed; Perna, Simone; Cetin, Demet; Suludere, Zekiye; Barras, Alexandre; Boukherroub, Rabah
Abstract: Plastics of different sizes (micro- and nano-sized) are often identified in aquatic environments. Nevertheless, their influence on marine organisms has not been widely investigated. In this study, the responses of the microalga Chlorella vulgaris to micro- and nanoplastics exposure were examined using long term toxicity test. The plastics tested were carboxyl-functionalized and non-functionalized polystyrene of 20, 50 and 500 nm in diameter. A reduction in algal cell viability and chlorophyll a concentration has been observed after exposure to the small sizes (20 and 50 nm) of plastics. Lactate dehydrogenase activity and reactive oxygen species concentration/production were significantly higher after exposure to the 20 nm nanoplastics than that of control confirming the stress condition. Fourier transform infrared (FTIR) spectroscopy analysis proved the attachment of nanoplastics to microalgae and rearrangement of extracellular polymeric substances. The cellular stress appeared as increased cell size, deformed cell wall and increased volume of starch grains. Graphical abstract: Unlabelled Image Highlights: 20, 50 and 500 nm polystyrene particles were tested on Chlorella vulgaris . Chlorella vulgaris revealed toxicity for small PS particles (20 and 50 nm). Reduction in cell viability, chlorophyll a concentration and increased ROS were observed. LDH and FTIR analyses showed cell wall damage. SEM and TEM examinations revealed PS particles adsorption onto microalgal cells.